Minat Baca Anak Usia Sekolah Dasar di Lingkungan Taman Bacaan Masyarakat Jayanti Palembang - Ramadaniah, Anisa Rizky; Hakim, Imron A. (Journal of Nonformal Education and Community Empowerment, 2018)
The Purpose of this study is to knowing interst of elementary students reading in the Taman Baca Mastayakat (TBM) Jayanti Palembang neighborhood.  This study uses quantitative descriptive method. The method of collecting the data is questionnaires, observation, and documentation. Method of taking the xamples is purposive xampling with 38th  respondents. As a results showed that elementary students have highly interest of reading, this is including aspects   1) Students attention to visiting that they realize how important is reading a book, 2) Good cover of books pay the attention to studying that book, 3) The pleasure of reading a book to finish it without any pressure from anyone, 4) Students give their times to reading a book or books in a day or a week, 5) After finish reading and understanding the book, hoping they will sharing with other friends, in the end it can be use full for everyone, and the present of TBM will stimulae to increasing interest of reading elementary students. This study recommendating or suggesting that the management of TBM to adding thier collections, more than books they have it more interesting people of the neighborhood not just elementary students to visiting and reading in TBM.